2005
DOI: 10.1016/j.gca.2005.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic mobility in the ambient sulfidic environment: Sorption of arsenic(V) and arsenic(III) onto disordered mackinawite

Abstract: Arsenate, As(V), sorption onto synthetic iron(II) monosulfide, disordered mackinawite (FeS), is fast. As(V) sorption decreases above the point of zero surface charge of FeS and follows the pH-dependent concentration of positively charged surface species. No redox reaction is observed between the As(V) ions and the mineral surface over the time span of the experiments. This observation shows that As(V) dominantly forms an outer-sphere complex at the surface of mackinawite. Arsenite, As(III), sorption is not str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
114
4
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(129 citation statements)
references
References 35 publications
9
114
4
1
Order By: Relevance
“…[3][4][5] Over time, extending up to two years in anoxic sediments, it transforms into greigite (Fe 3 S 4 ), pyrrhotite [hexagonal or monoclinic Fe (1-x) S, 0 < x < 0.2], pyrite (FeS 2 ), or, depending on redox conditions, elemental S and Fe. [6][7][8][9] Mackinawite is known to influence the mobility and bioavailability of environmentally-important trace elements, notably through processes involving either sorption 10,11 or oxidative dissolution, [12][13][14] and it figures in the well-known iron-sulfur hypothesis on the origin of life. 15 Very recently, Nakamura et al 16 demonstrated that cell-enmeshed assemblies of mackinawite produced by the Fe-reducing bacterium, Shewanella loihica PV-4, function efficiently as electron-transfer conduits and, therefore, have potential for use as bioanode materials in microbial fuel cells.…”
Section: Mackinawite (Tetragonal Fes)mentioning
confidence: 99%
“…[3][4][5] Over time, extending up to two years in anoxic sediments, it transforms into greigite (Fe 3 S 4 ), pyrrhotite [hexagonal or monoclinic Fe (1-x) S, 0 < x < 0.2], pyrite (FeS 2 ), or, depending on redox conditions, elemental S and Fe. [6][7][8][9] Mackinawite is known to influence the mobility and bioavailability of environmentally-important trace elements, notably through processes involving either sorption 10,11 or oxidative dissolution, [12][13][14] and it figures in the well-known iron-sulfur hypothesis on the origin of life. 15 Very recently, Nakamura et al 16 demonstrated that cell-enmeshed assemblies of mackinawite produced by the Fe-reducing bacterium, Shewanella loihica PV-4, function efficiently as electron-transfer conduits and, therefore, have potential for use as bioanode materials in microbial fuel cells.…”
Section: Mackinawite (Tetragonal Fes)mentioning
confidence: 99%
“…The penta-valent As is more toxic than the tri-valent As [6]. Surface mediated redox process of As(V) and As(III) on Fe-sulfide mineral surfaces, such as pyrite [7] and mackinawite [8], are unexplored and not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Under certain conditions pyrrhotite (Fe 1 − x S) can also form in anoxic sediments (Horng and Roberts, 2006;Larrasoana et al, 2007) (Table 1). In addition to their geological significance, iron sulfide minerals can be used in soil or water remediation: mackinawite was shown to effectively immobilize heavy metals and toxic ions through sorption mechanisms (Watson et al, 1995;Holmes, 1999;Mullet et al, 2004;Livens et al, 2004;Wolthers et al, 2005;Liu et al, 2008;Gallegos et al, 2008;Renock et al, 2009).…”
Section: Introductionmentioning
confidence: 99%